Long-term follow-up of incident acute coronary syndrome: results from the French MONICA registries over the 2009-2017 period. (11th May 2022) - Gauthier, V; Lafrance, M; Barthoulot, M; Rousselet, L; Montaye, M; Ferrieres, J; Huo Yung Kai, S; Biasch, K; Moitry, M; Amouyel, P; Dallongeville, J; Meirhaeghe, A
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Univ. Lille, Inserm, CHU Lille, Institut Pasteur de Lille, Santé Publique France, U1167 - RID-AGE - Facteurs de risque et déterminants moléculaires des maladies liées au vieillissement, Lille, France. Background: The prognosis of an acute coronary syndrome (ACS) is strongly affected by the clinical, biological, and angiographic features of the event. However, few studies have characterized long-term recurrences of ACS after an incident (first) event. Aim: The goals of this study were (i) to estimate the long-term (9 years) risk of ACS recurrence, including fatal ACS recurrence, among survivors of a first-ever ACS, according to its diagnosis subtype (STEMI / NSTEMI / Unstable angina (UA)) and (ii) to identify factors associated with these risks. Methods: We assessed all men and women (aged 35-74) hospitalized between January 2009 and December 2016 for an incident (first-ever) ACS, in the 3 distinct geographical areas covered by the MONICA registries in the north, east and south-west of France, and still alive at discharge (Index event). ACSs were classified as STEMI, NSTEMI and UA. Patients were followed-up until December 2017. Recurrent events were defined as the first non-fatal or fatal ACS occurring after hospital discharge from the index event. Multivariate Cox regression models were used to assess the relationships between recurrent ACS and variables of interest. Results: A total of 15, 739 incident ACSs were included. The study comprised a total of 63, 777 patients-years and a median duration of follow-up of 3.8 [1.6-6.0] years. There were 1, 963 (12, 4%) recurrent ACSs of which almost half (1, 046; 53%) occurred during the first year. The 1-, 5- and 9- year cumulative probabilities of recurrent ACS were 6.7% [6.3-7.1%], 13.4% [12.8-14.0%] and 18.4% [17.4-19.5%], respectively, and those of fatal recurrent ACS were 1.4% [1.2-1.5%], 2.7% [2.3-3.0%] and 4.3% [3.6-4.9%], respectively. Annual 1-year recurrence rates decreased between 2009 and 2016, from 7.4% to 4.0% (p Cochran-Armitage test <0.001). After an index STEMI and NSTEMI, the most frequent form of recurrent event was a NSTEMI, whereas UA was more likely event after an index UA. The age at the time of the event, the geographical region (North to South gradient), the presence of a major event (i.e. resuscitated cardiac arrest, acute pulmonary oedema or cardiogenic shock), and an impaired left ventricular ejection fraction (LVEF) were significantly associated with the risk of recurrence and fatal recurrence. ACS subtype was not associated with recurrent risk after adjustment for confounders. Conclusions: In conclusion, after an incident ACS the recurrence rate remained elevated, with one in five patients experiencing a recurrent ACS during a 9-years follow-up. Half of recurrent events occurred within the first year after the index event and NSTEMI was the most frequent form of recurrent event. Age at the time of the event, region, major event and impaired LVEF are factors associated with a higher risk of recurrence, the most important one being an LVEF <35%.